Preventing opioid prescribing for low back pain using multimodal mechanical stimulation vs. TENS: a randomized-controlled trial - Amy L. Baxter; Amy L. Baxter; Jena L. Etnoyer-Slaski; Jessica Allia Rice Williams; Kevin Swartout; Lindsey L. Cohen; M. Louise Lawson (Frontiers in Pain Research, 2025)
BackgroundLow back pain (LBP) is the most common reason for outpatient opioid prescribing: a quarter of patients receive prescriptions, leading to opioid use disorder (OUD) in 5%. Guideline-recommended multimodal interventions often face implementation barriers, and effective modalities (e.g., electrical stimulation) lack coverage. A multimodal mechanical stimulation (M-Stim) device for LBP has demonstrated safety and efficacy in pain reduction, but its impact on opioid use has not yet been determined.MethodsAs part of an NIH-funded double-blind study to reduce pain and opioid use, patients with moderate-to-severe LBP presenting to two suburban chiropractic centers were randomized to receive either the M-Stim device or a transcutaneous electrical nerve stimulation (TENS) unit for 30 min daily, in addition to other therapies. Analgesic use was reported daily for 28 days, with new prescribing followed weekly for 3 months. The primary outcome was prescribing in the opioid-naïve subjects. Secondary endpoints included risk factors for prolonged use in the opioid-naïve subjects, milligram morphine equivalents (MME) for opioid users between the first and last 2 weeks, and prescribing compared with national rates.ResultsAfter informed consent, 159 eligible patients were randomized to M-Stim (87) or TENS (72) (mean age 42.6 years, 54% female, BMI 30.9, NRS 5.5) between 23 June 2022 and 31 December 2023. Zero opioid-naïve M-Stim participants (n = 43) received prescriptions (0% vs. 8.6%, Fisher's exact p = 0.086), and those taking opioids used significantly fewer MME [7.5 (SD 3.54) vs. 498.5 MME (SD 474.9), p < 0.0001] for fewer of reported days [M-Stim 2/47 (4.2%)] compared with TENS [n = 36, 38/102 (37%), RR 0.11 (95% CI 0.28–0.44), p = 0.0018]. M-Stim significantly reduced MME in opioid users [−44.6% (32.33 MME), p = 0.02], use days for those with BMI ≥30 [−3 (99% CI −5.73 to −0.26), p = 0.032], and prescribing compared with national rates [9.8% vs. 25%, −63%, RR 0.32 (95% CI 0.16–0.66), p = 0.002] while TENS did not.ConclusionsAmong chiropractic patients with moderate-to-severe LBP, added use of a multimodal M-Stim device in the opioid-naïve subjects significantly reduced factors associated with OUD compared with TENS and reduced use days for those with BMI ≥30. This novel device is a potential alternative to prescribing opioids as first line for LBP management.Clinical Trial Registrationhttps://clinicaltrials.gov/study/NCT04491175, identifier NCT04491175.